2016
DOI: 10.3892/etm.2016.3378
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of various continued antiplatelet therapies in patients who were administered DAPT following the implantation of drug-eluting stents and developed gastrointestinal hemorrhage

Abstract: Abstract. Although an increasing number of patients accept dual antiplatelet therapy (DAPT) following implantation of drug-eluting stents (DES) for coronary heart disease (CHD), the proportion of patients with DAPT who subsequently develop gastrointestinal hemorrhage continues to increase. To ensure the clinical outcomes from DES, it is important to formulate a novel continued antiplatelet therapy for patients who were administered DAPT and subsequently develop gastrointestinal hemorrhage following DES implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Dual antiplatelet therapy can significantly reduce mortality, the incidence of adverse ischemic events, short-term and long-term complications after PCI and the incidence of other major adverse cardiovascular events, but it also undoubtedly increases the risk of GIB. 14 , 15 It has been reported that the incidence of in-hospital GIB in patients with AMI was 1.19%, even up to 10.4% within 4 years in STEMI patients after primary PCI. 16 , 17 Severe bleeding after acute coronary syndrome (ACS) can increase the mortality by 5 times, GIB was an independent predictor of mortality in patients with AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Dual antiplatelet therapy can significantly reduce mortality, the incidence of adverse ischemic events, short-term and long-term complications after PCI and the incidence of other major adverse cardiovascular events, but it also undoubtedly increases the risk of GIB. 14 , 15 It has been reported that the incidence of in-hospital GIB in patients with AMI was 1.19%, even up to 10.4% within 4 years in STEMI patients after primary PCI. 16 , 17 Severe bleeding after acute coronary syndrome (ACS) can increase the mortality by 5 times, GIB was an independent predictor of mortality in patients with AMI.…”
Section: Discussionmentioning
confidence: 99%
“…The controller allows movements of 2 mm and changes the viewing angle by 3° in a three-dimensional space. More recently, multicentre studies have demonstrated that MCE controlled by a robot magnet achieved 93.4% accuracy in detecting focal lesions in the stomach compared with standard gastroscopy 24 30…”
Section: Methodsmentioning
confidence: 99%
“…Clopidogrel is a platelet aggregation inhibitor used for the treatment of acute coronary syndrome and chronic vascular stenosis. While dual antiplatelet therapy decreases cardiovascular events after successful coronary drug-eluting stenting, it is considered to increase the risk of gastrointestinal bleeding [ 1 ]. There are no previous reports of small bowel injury due to clopidogrel.…”
Section: Introductionmentioning
confidence: 99%